TLR3/TAK1 signalling regulates rhinovirus-induced interleukin-33 in bronchial smooth muscle cells. Issue 4 (5th October 2020) - Ramu, Sangeetha; Calvén, Jenny; Michaeloudes, Charalambos; Menzel, Mandy; Akbarshahi, Hamid; Chung, Kian Fan; Uller, Lena
Background: Asthma exacerbations are commonly associated with rhinovirus (RV) infection. Interleukin-33 (IL-33) plays an important role during exacerbation by enhancing Type 2 inflammation. Recently we showed that RV infects bronchial smooth muscle cells (BSMCs) triggering production of interferons and IL-33. Here we compared levels of RV-induced IL-33 in BSMCs from healthy and asthmatic subjects, and explored the involvement of pattern-recognition receptors (PRRs) and downstream signalling pathways in IL-33 expression. Method: BSMCs from healthy and severe and non-severe asthmatic patients were infected with RV1B or stimulated with the PRR agonists poly(I:C) (Toll-like receptor 3 (TLR3)), imiquimod (TLR7) and poly(I:C)/LyoVec (retinoic acid-inducible gene 1 (RIG-I)/melanoma differentiation-associated protein 5 (MDA5)). Knockdown of TLR3, RIG-I and MDA5 was performed, and inhibitors targeting TBK1, nuclear factor-κB (NF-κB) and transforming growth factor (TGF)-β-activated kinase 1 (TAK1) were used. Gene and protein expression were assessed. Results: RV triggered IL-33 gene and protein expression in BSMCs. BSMCs from patients with non-severe asthma showed higher baseline and RV-induced IL-33 gene expression compared to cells from patients with severe asthma and healthy controls. Furthermore, RV-induced IL-33 expression in BSMCs from healthy and asthmatic individuals was attenuated by knockdown of TLR3. Inhibition of TAK1, but not NF-κB or TBK1, limited RV-induced IL-33. The cytokine secretion profile showed higher production of IL-33 in BSMCs from patients with non-severe asthma compared to healthy controls upon RV infection. In addition, BSMCs from patients with non-severe asthma had higher levels of RV-induced IL-8, TNF-α, IL-1β, IL-17A, IL-5 and IL-13. Conclusion: RV infection caused higher levels of IL-33 and increased pro-inflammatory and Type 2 cytokine release in BSMCs from patients with non-severe asthma. RV-induced IL-33 expression was mainly regulated by TLR3 and downstream via TAK1. These signalling molecules represent potential therapeutic targets for treating asthma exacerbations. Rhinovirus-induced IL-33 is overexpressed in bronchial smooth muscle cells from asthmatics, and the production of IL-33 following infection is mediated by activation of TLR3 and downstream TAK1 signalling https://bit.ly/3fXH0h3